A study on the effects of personality traits on career adaptability in Carigali Hess Operating Company / Ahmad Syarafi Adli Azami - Adli Azami, Ahmad Syarafi (Faculty of Business and Management, 2019)
As it becomes more common for individuals to work in many different jobs throughout their lives, career adaptability becomes much more essential to comprehending how individuals cope with changing working environment that more often than not, occurs in constant setting. The research intends to investigate the relationship between personality traits and career adaptability. A total of 127 employees from Carigali Hess Operating Company completed the Career Futures Inventory – Revised and a Big Five measure from the International Personality Item Pool to examine potential relationships between individual personality traits and career adaptability. The variables drawn from this study are the personality traits namely; Openness, Conscientiousness, Extraversion, Agreeableness and Neuroticism. The sample drawn was by using the probability sampling; simple random method. The data collection process was done through two phases of collection. Pearson’s Correlation Analysis, Frequency analysis and regression analysis were done among the variables and it was found that the variables had all influenced career adaptability by 46.4 % while the rest could be explained by variables outside the study. The study found that there exists influence between personality traits and Career Adaptability. Through this findings, it was recommended to the company to implement any forms of policies to encourage the traits depending on the direction of the traits to influence Career Adaptability.